2013
DOI: 10.1021/nl402124h
|View full text |Cite
|
Sign up to set email alerts
|

Au–Cu2–xSe Heterodimer Nanoparticles with Broad Localized Surface Plasmon Resonance as Contrast Agents for Deep Tissue Imaging

Abstract: We report a new type of heterogeneous nanoparticles (NPs) composed of a heavily doped semiconductor domain (Cu2-xSe) and a metal domain (Au), which exhibit a broad localized surface plasmon resonance (LSPR) across visible and near-infrared (NIR) wavelengths, arising from interactions between the two nanocrystal domains. We demonstrate both in vivo photoacoustic imaging and in vitro dark field imaging, using the broad LSPR in Cu2-xSe-Au hybrid NPs to achieve contrast at different wavelengths. The high photoacou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
156
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(157 citation statements)
references
References 52 publications
(64 reference statements)
1
156
0
Order By: Relevance
“…A step forward in this direction has been made by Liu et al, who synthesized Au-Cu 2Àx Se heterostructures and demonstrated their use as contrast agents in dark field and photoacoustic imaging. 61 One reason for using plasmonic NCs as markers for imaging is the possibility to leverage the enhancement of the non-linear optical processes near the surface of the NCs. Unfortunately, the near field enhancement (NFE) from copper chalcogenide NCs is expected to be much lower than that of noble metal NCs, due to the smaller number of free carriers, which in principle makes them less suitable than noble metal NCs for applications such as surface enhanced Raman scattering, metal enhanced fluorescence and plasmonic solar cells.…”
Section: Review Article Chem Soc Revmentioning
confidence: 99%
“…A step forward in this direction has been made by Liu et al, who synthesized Au-Cu 2Àx Se heterostructures and demonstrated their use as contrast agents in dark field and photoacoustic imaging. 61 One reason for using plasmonic NCs as markers for imaging is the possibility to leverage the enhancement of the non-linear optical processes near the surface of the NCs. Unfortunately, the near field enhancement (NFE) from copper chalcogenide NCs is expected to be much lower than that of noble metal NCs, due to the smaller number of free carriers, which in principle makes them less suitable than noble metal NCs for applications such as surface enhanced Raman scattering, metal enhanced fluorescence and plasmonic solar cells.…”
Section: Review Article Chem Soc Revmentioning
confidence: 99%
“…While metallic nanostructures of Au 8,9 and Ag 10 are well known plasmonic materials for the visible region with applications in photovoltaics, sensing, and tissue imaging, doped semiconductor nanostructures 11 are important for NIR plasmonics with a significant role in NIR detectors 12 and deep tissue imaging. 13 However, the nonlinear optical properties of semiconductor nanomaterials having NIR plasmonic applications are not well explored yet. Among semiconducting nanoparticles, transition metal chalcogenides stand out for the reason that they can form variety of stoichiometric compounds with variable optical band gaps.…”
mentioning
confidence: 99%
“…[15][16][17][18][19][20] In this letter, we developed a near-real-time virtual intraoperative surgical photoacoustic microscope (VISPAM) by integrating PAM and conventional surgical microscopy. The VISPAM system could obtain, process, and display both PAM and microscopic images at the same time.…”
Section: -5mentioning
confidence: 99%
“…[12][13][14] Because PAM can provide label-free optical absorption information in a non-invasive manner with high contrast and resolution, this modality has widely been used to image tumor angiogenesis, tumor metabolism, brain function, ocular structures, molecular information, etc. [15][16][17][18][19][20] In this letter, we developed a near-real-time virtual intraoperative surgical photoacoustic microscope (VISPAM) by integrating PAM and conventional surgical microscopy. The VISPAM system could obtain, process, and display both PAM and microscopic images at the same time.…”
mentioning
confidence: 99%